Urgensi Bahasa Arab Bagi Siswa Kelas Khusus Penghafal Qur'an di MTs Al-Muhajirin - Lembang - Muhammad Utsman Fauzi Abdurrozzaq; Nadya Azzahra Nabila; Aghnia Khairunnisa; Rengganis Attiya Layla Burhan; Ahmad Fu'adin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Arabic and the Koran are two interrelated things because Arabic is used as a language in the Koran. Studying Arabic is not only an existing subject, but also a form of worship that can be done, because Arabic is the main requirement for reading the Koran. Apart from reading, Muslims are also encouraged to memorize, understand, and practice what is contained in the Koran. Of course, to do these four things requires mastery of the language used, namely Arabic. The purpose of this article is to examine whether learning Arabic has an important role for memorizers of the Qur'an in special classes for memorizing the Qur'an at MTs Al Muhajirin-Lembang. The type of research used is research that is descriptive analysis, namely with a qualitative approach. The main data collection technique used is observation techniques. From observations carried out directly at MTs Al Muhajirin and assisted by various journal references, the author found a correlation or relationship between learning Arabic and memorizing the Al-Qur'an and the important role it plays in it. The existence of this research also influences people who previously did not understand the urgency of Arabic for memorizing the Quran and Muslims.